Thai language Teaching Model Based on Thai Linguistics Concept and an Experience-Based Approach with Technology-Enhanced Language Learning (TELL) to Resolve the Thai Pronunciation Problem in Ethnic Students - Suradacha, Kasama; Khunmathurot, Songphop; Ketpan, Jutharat; Topithak, Krittayakan (Ratchaphruek Journal, 2025)
This research aimed to: 1) investigate Thai pronunciation difficulties among ethnic students; 2) develop and determine the quality of a teaching model; 3) study the effectiveness of the model; and 4) evaluate the model. The study sample included 15 lecturers from the Faculty of Education at Kamphaeng Phet Rajabhat University and 17 second- and third-year ethnic students from Thai Language, Primary Education, and Social Studies programs. Additionally, 12 experts were involved in model validation. Tools utilized included document analysis, interviews, a pronunciation ability test, model assessment forms, an experimental results recording form, a satisfaction survey, and a focus group form. Statistical analysis employed percentage, mean, standard deviation, and the t-test. Key findings are as follows: 1) Thai pronunciation challenges among ethnic students encompassed difficulties in articulating consonants, vowels, and tones, 2) The developed Thai language teaching model consists of (1) principles, (2) objectives, (3) teaching and learning processes, (4) roles of learners and teachers, and (5) measurement and evaluation, 3) The ethnic students’ Thai pronunciation ability was significantly higher after using the model compared to before, at the .05 statistical level, and 4) Students reported the highest overall level of satisfaction with the developed model.